2017
DOI: 10.1080/21548331.2017.1359060
|View full text |Cite
|
Sign up to set email alerts
|

Update in perioperative medicine: practice changing evidence published in 2016

Abstract: This summary reviews 18 key articles published in 2016 which have significant practice implications for the perioperative medical care of surgical patients. Due to the multi-disciplinary nature of the practice of perioperative medicine, important new evidence is published in journals representing a variety of medical and surgical specialties. Keeping current with the evidence that drives best practice in perioperative medicine is therefore challenging. We set out to identify, critically review, and summarize k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…4,32 With continually changing guidelines on management of chronic conditions, such as atrial fibrillation and anti-platelet therapy for stable ischemic heart disease, the incidence of perioperative MI or CAR is likely to remain in flux. 33 Finally, the definition of MI continues to evolve, and many investigators have advocated lower thresholds of troponin and early intervention upon detection of postoperative MIs. 25 To our knowledge, this study is the first to report the influence of hospital volume on cost and duration of stay after MI or CAR for major abdominal operations.…”
Section: Discussionmentioning
confidence: 99%
“…4,32 With continually changing guidelines on management of chronic conditions, such as atrial fibrillation and anti-platelet therapy for stable ischemic heart disease, the incidence of perioperative MI or CAR is likely to remain in flux. 33 Finally, the definition of MI continues to evolve, and many investigators have advocated lower thresholds of troponin and early intervention upon detection of postoperative MIs. 25 To our knowledge, this study is the first to report the influence of hospital volume on cost and duration of stay after MI or CAR for major abdominal operations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an increased risk of bleeding and thromboembolic events in patients undergoing bridging therapy. [50][51][52][53][54][55] This decision must be discussed with the physician prescribing the warfarin.…”
Section: Balancing Thromboembolic and Bleeding Risksmentioning
confidence: 99%
“…Их использование позволяет существенно повысить уровень обезболивания, улучшить качество жизни пациентов, а также снизить потребность в опиоидных анальгетиках. «Опиоид-сберегающее» действие НПВП позволяет уменьшить частоту НЯ, связанных с наркотическими препаратами: тошноты, рвоты, избыточной седации и нарушения перистальтики кишечника [55][56][57].…”
Section: эффек тивность нестероидных противовоспалительных препаратовunclassified